2005
DOI: 10.1002/jcc.20330
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spectroscopic constants for diatomic molecules in the ground and excited states using time‐dependent density functional theory

Abstract: Spectroscopic constants of the ground and next seven low-lying excited states of diatomic molecules CO, N2, P2, and ScF were computed using the density functional theory SAOP/ATZP model, in conjunction with time-dependent density functional theory (TD-DFT) and a recently developed Slater type basis set, ATZP. Spectroscopic constants, including the equilibrium distances r(e), harmonic vibrational frequency omega(e), vibrational anharmonicity omega(e)x(e), rotational constant B(e), centrifugal distortion constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
3
13
0
1
Order By: Relevance
“…The overall agreement with experiment is not bad, although the occasional discrepancies of ca. 1 eV are considerably larger than what has been found in other TD-DFT calculations of valence excitation energies using SAOP [15,22,39,40,45]. Each molecule has its own characteristic spectrum.…”
Section: Figure 2 Calculated X-ray Absorption Spectrum Ofmentioning
confidence: 83%
See 1 more Smart Citation
“…The overall agreement with experiment is not bad, although the occasional discrepancies of ca. 1 eV are considerably larger than what has been found in other TD-DFT calculations of valence excitation energies using SAOP [15,22,39,40,45]. Each molecule has its own characteristic spectrum.…”
Section: Figure 2 Calculated X-ray Absorption Spectrum Ofmentioning
confidence: 83%
“…We have demonstrated that TD-DFT with the SAOP exchange-correlation potential can predict reliable vertical excitation energies [15,22,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…2 in the molecule. [8] Therefore,C Ob inds preferentially through donor-acceptor interactions A!B. [7] Thed ifferent bonding situation compared with linear allene H 2 C=C=CH 2 ,w hich has ad eep potential well, can be rationalized with the 3 B 1 triplet ground state of CH 2 ,which preferentially engages in normal covalent ("electron-sharing") bonds A À B.…”
mentioning
confidence: 99%
“…In addition, two of the excited electronic states, B 3 Π g and W 3 Δ u , are of special interest, because their potential energy curves (PECs) nearly coincide and thus give rise to peculiar spectral behavior 4. Therefore, the spectroscopic and molecular properties of the N 2 have become the subject of extensive studies in the past several decades, both experimentally 1–3, 5–11 and theoretically 4, 12–27.…”
Section: Introductionmentioning
confidence: 99%